Hubungan Pola Makan dan Aktivitas Fisik Dengan Status Gizi Siswi Kelas VII SMP Negeri (Full Day School) - Katmawanti, Septa; Supriyadi, Supriyadi; Setyorini, Inung (citeus, 2019)
The government's effort to improved the quality of education is through full day school program.Full day school starts in the morning until the afternoon.A relatively long time requires the students to follow all the learning activities in the school, resulting in the activities of the students become dense so that it affects the difficulties of students in setting the time of rest and pattern of eating.An irregular diet can have an impact on the nutritional status of schoolgirls.This research was conducted to know the relationship of dietaryhabitand physical activity with the nutritional status of Class VII SMP Negeri full day school, Malang. The draft on this study uses correlational research methods with a cross sectional research design. Samples used as many as 100 girls with stratified random sampling technique.Data analysis using Spearman correlation test. The results of this study showed a significant linkbetween dietary habitand nutritional status of studentswith P value 0.000 and correlation coefficient of 0.406.Also indicates a significant relationship between physical activity andnutritional status of studentwith P value 0.000 and correlation coefficient of-0.348.